Case Report: Abnormalities of sperm motility and morphology in a patient with Leber hereditary optic neuropathy: Improvement after idebenone therapy - Orssaud, Christophe; Barraud Lange, Virginie; Wolf, Jean Philippe; LeFoll, Nathalie; Soufir, Jean Claude (Frontiers in Neurology, 2023)
Case We report the sperm characteristics of a male patient who developed, when he was 18 years old, a Leber hereditary optic neuropathy, a hereditary optic neuropathy due to mtDNA mutation as well as variants in the nuclear DNA. At the age of 30 years-old, he complained of infertility lasting for 2 years. Semen analyses showed low motility spermatozoa and a high percentage of morphological or ultrastructural abnormalities. Levels of epididymal markers were strongly atypical. Idebenone was prescribed as treatment of his Leber hereditary optic neuropathy in order to improve his visual acuity. After 5 months of this treatment, motility of spermatozoa increased, and their vitality improved. A natural conception occurred. Outcome This case is the first description of an anomaly of spermatozoas and of the epididymis epithelium in a patient with Leber hereditary optic neuropathy. It draws attention to sperm pathologies in patients with mitochondrial disorders. The role of the mtDNA mutations must be suspected since it plays an important role in the development and motility of spermatozoa. In addition, idebenone can by-pass the complex I and transfer electrons to complex III. It has been suspected to have a favorable effect on spermatogenesis. Conclusion This case confirms the possibility of sperm dysfunction in Leber hereditary optic neuropathy and the interest of idebenone as a treatment for infertility due to mtDNA mutations in human.